An RF breast coil for 0.2T MRI. Issue 1 (12th November 2015) - Blasiak, Barbara; Volotovskyy, Vyacheslav; Tyson, Randy; Sharp, Jonathan; Tomanek, Boguslaw
ABSTRACT: Breast cancer is the most frequently diagnosed cancer in women. High field studies have shown the diagnostic value of breast MRI, but the examination costs greatly exceed those of competing conventional mammography. Low field MRI offers typical MRI contrast at substantially lower cost, but has suffered from lower spatial resolution. Specificity of breast MRI can potentially be increased by acquiring MR imaging with higher spatial or temporal resolution, but the signal‐to‐noise ratio (SNR) achievable in a given imaging time becomes limiting. SNR for the particular pulse sequence and magnet field strength is strongly influenced by the characteristics of the radio‐frequency coil. An optimal breast coil should yield excellent SNR but also generate a homogeneous B1 field, while allowing imaging of the both breasts simultaneously and maintaining patient comfort. RF receiver coil design is a key determinant of image quality, thus to address this we have designed and constructed a low field breast imaging coil. The coil was tested with a 4‐post 0.2T MRI providing high quality breast images. Designed and constructed saddle rf coil allows to obtain good quality image of the breast using low 0.2 T MRI system within 2 minutes. The coil provides patient comfort as breast compression is not required and minimizes artefacts caused by respiration or motion. A high contrast, low‐cost and pain‐free breast examination using optimized low field MRI system has the potential to serve a large patient population for whom current technologies have deficiencies. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 46B: 3–7, 2016